Assessment of Asthmatic Patients’ Quality Of Life in Jordan Fadel Hazza’ Ali al-Mahameed.* - Ali, fadel; Gorgies, Samira (Iraqi National Journal of Nursing Specialties, 2005)
Abstract A descriptive study was conducted in Al-Bashir teaching hospital in Amman city from 15th May 2004 to 15th August 2004 , in order to "Assess the adult asthmatic patients’ quality of life (QOL). Objective: This study aimed at identifying the domains of (Environmental, Physical, Daily Living Activity, Drug and Medication, Psychological , and Social), Methodology : A Purposive (Non-Probability) sample of (100) adult asthmatic patients visited the emergency department and outpatient clinic of chest department in Al-bashir hospital .A Questionnaire was constructed for the purpose of the study, and comprised of (2) parts, consist of ( 108 ) items, that include (1) demographic characteristics form,(2) the assessment of adult asthmatic patients’ QOL domains. Reliability and validity of the questionnaire was determined through internal consistency through a pilot study, content validity of the questionnaire was determined through panel of experts . Data was collected by the investigator who interviewed those patients and filled out the constructed questionnaire forms. Data analysis by using (Percentage, Frequencies, Mean of scores) and inferential statistical analysis [Pearson correlation, T-Test, One way analysis of variance (ANOVA)]. Results : The findings of the study indicated that the quality of life for patients had greatly effected during the items, respiratory system cardio vascular system as a part of physical domains, also psychology domains and social domains. Recommendations : The study recommended that the Jordan Ministry of Health would be helpful in providing, building or developing the places and centers of chest departments or it’s hospitals that provide care, also an educational program to be developed, and implemented for adult asthmatic patients in order to increase their actual knowledge . Key words : Adult Asthmatic, Quality of life